Dampak Kenaikan PPN 12% terhadap Pendapatan Negara dan Kesejahteraan Masyarakat - Aisyah Aulia; Siti Maisaroh; Assyfa Futri Ananta; Wahjoe Pangestoeti (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This study examines the impact of the 12% VAT increase on state revenue and societal welfare in Indonesia. The research aims to analyze how the policy affects economic indicators such as inflation, purchasing power, and fiscal stability. A qualitative method with a systematic literature review approach was employed, utilizing data from scholarly articles, online news, and related journals. Findings indicate that the VAT increase contributes to a 0.8–1% rise in the Consumer Price Index (CPI) and significantly affects secondary and tertiary goods, while essential goods remain exempt. The policy is expected to enhance state revenue, enabling greater fiscal space for social and infrastructure programs. However, it also raises concerns about reduced purchasing power, particularly among low-income groups. The study suggests implementing compensatory mechanisms and targeted subsidies to mitigate adverse effects. This research underscores the importance of balancing fiscal goals with social equity.